Guidelines for Regulated Cell Death Assays: A Systematic Summary, A Categorical Comparison, A Prospective - Hu, Xi-min; Li, Zhi-xin; Lin, Rui-han; Shan, Jia-qi; Yu, Qing-wei; Wang, Rui-xuan; Liao, Lv-shuang; Yan, Wei-tao; Wang, Zhen; Shang, Lei; Huang, Yanxia; Zhang, Qi; et al. (Frontiers in Cell and Developmental Biology, 2021)
Over the past few years, the field of regulated cell death continues to expand and novel mechanisms that orchestrate multiple regulated cell death pathways are being unveiled. Researchers, meanwhile, distributed themselves to targeting these regulated pathways that are closely associated with various diseases for diagnosis, treatment, and prognosis. However, the complexity of the mechanism and the difficulties of distinguishing among various regulated types of cell death make it harder to carry out the work and delays its progression. Here, we provide a systematic guideline for the fundamental detection and distinction of the major regulated cell death pathways following morphological, biochemical, and functional perspectives. Moreover, comprehensive evaluation of different methods is critically reviewed, helping researchers to make a reliable selection from among the cell death assays. Also, we highlight the recent events that have demonstrated some novel regulated cell death processes, including newly reported biomarkers (e.g., non-coding RNA, exosomes, and proteins) and detection techniques.